Understanding CO2 Emissions from Geothermal Power Generation in Turkey - Idrissi, Oumaima; Orucu, Yasemin; Hallgrimsdottir, Elin; Mateos Merino, Almudena; Akin, Serhat; Idrissi, Oumaima (World Bank, Washington, DC, 2021)
Carbon dioxide (CO2) emission factors from Turkish geothermal plants have been measured in the 400 to 1,300 gram per kilowatt-hour (g per kWh) range, significantly higher than the reported global average (121 g per kWh). The good news is that despite these unusually high initial emission factors most, if not all, Turkish geothermal power plants show a steady decline in CO2 emissions over time. Predictive models developed under the World Bank-financed Geothermal Development Project show that estimated average lifetime emissions from Turkey’s geothermal power plants are aligned with the global average. These results justify further investments in the development of geothermal energy in Turkey, along with additional research on how best to manage CO2 emissions.